Foramen of Vesalius: Prevalence, Morphology, Embryological Basis and Clinical Implications - Murlimanju BV.; Reddy GR.; Latha VP.; Vasudha VS.; Rao CP.; Mangala MP.; Ashwin K.; Rajanigandha V. (Department of Surgery, UKM Medical Centre, 2015)
The objectives of the present study were to find the prevalence of foramen of Vesalius and to discuss its morphology. The embryological basis of this foramen and its surgical highlights are emphasized. The study comprised 78 human adult dried skulls, which were obtained from the anatomy laboratory of our institution. The greater wing of the sphenoid bone was macroscopically observed for the presence of foramen of Vesalius. It was observed that the foramen was present in 29 skulls (37.2%). It was seen bilaterally in 13 (16.7%) skulls and unilaterally in 16 (20.5%) specimens.Anatomical literature has explained the variation of this foramen by the developmental considerations. We believe that the details of this foramen are known to have significant implications for the medical and surgical literature. The details are also enlightening to the clinical anatomists and other broad specialties of medicine.This sphenoidal emissary foramen contains a bridging vein, which connects the pterygoid venous plexus with the cavernous sinus. This communication is clinically important, since an extra cranial infection may sometimes reach the cavernous sinus through this foramen, which may lead to cavernous sinus thrombosis. Foramen of Vesalius can get injured during the trigeminal nerve block technique performed for the trigeminal neuralgia. In this procedure, the foramen can get hurt by a displaced instrument, which would end up in intracranial bleeding, which can spread the extracranal infection into the cavernous sinus. This may lead to serious disorders like Tolosa Hunt and Gradenigo syndromes.